Antiproliferative effect and ultrastructural alterations induced by psilostachyin on trypanosoma cruzi - Sülsen, Valeria Patricia (2010)
The effect of psilostachyin, a natural sesquiterpene lactone, on the growth and viability of cultured epimastigotes of Trypanosoma cruzi (Tulahuen) is reported. The antiproliferative effect was evaluated by counting the parasites in a Neubauer chamber and measuring their viability by using the dye exclusion technique. The effect on parasite growth was irreversible at concentrations higher than 1.0 μg/mL and the addition of glutathione only partially blocked the effect of the compound. Moreover, we have studied the effects of this natural compound on parasite ultrastructure by transmission electron microscopy. Interestingly, psilostachyin induced ultrastructural alterations on the parasites at a concentration of 0.5 μ,g/mL, with important mitochondrial swelling and deformity of the kinetoplast.